2021
DOI: 10.1111/jpn.13536
|View full text |Cite
|
Sign up to set email alerts
|

Elongase of very long chain fatty acids 6 (ELOVL6) promotes lipid synthesis in buffalo mammary epithelial cells

Abstract: Recent studies have shown elongase of very‐long‐chain fatty acids 6 (ELOVL6) is a vital protein for endogenous synthesis of saturated and monounsaturated long‐chain fatty acids in some mammals. Nevertheless, its role in lipid synthesis in buffalo mammary gland is still unclear. In this work, the full‐length coding sequence (CDS) of ELOVL6 was cloned and identified from buffalo mammary gland. As a result, the CDS of this gene is 795 bp, which encodes a polypeptide of 264 amino acid residues. The buffalo ELOVL6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Buffalo mammary epithelial cells (BuMECs) were obtained from a lactating buffalo (60 d postpartum; 5-year-old) and purified based on the differential sensitivity of the cells to trypsin digestion as previously described by our lab 39 , 40 . Dulbecco modified Eagle medium (Gibco, USA) supplemented with 5 μg/mL insulin (Sigma, USA), 5 μg/mL hydrocortisone (Sigma), 1 μg/mL epidermal growth factor (Sigma), 2% penicillin/streptomycin (Gibco) and 10% fetal bovine serum (Gibco) were used for the culture of purified BuMECs.…”
Section: Methodsmentioning
confidence: 99%
“…Buffalo mammary epithelial cells (BuMECs) were obtained from a lactating buffalo (60 d postpartum; 5-year-old) and purified based on the differential sensitivity of the cells to trypsin digestion as previously described by our lab 39 , 40 . Dulbecco modified Eagle medium (Gibco, USA) supplemented with 5 μg/mL insulin (Sigma, USA), 5 μg/mL hydrocortisone (Sigma), 1 μg/mL epidermal growth factor (Sigma), 2% penicillin/streptomycin (Gibco) and 10% fetal bovine serum (Gibco) were used for the culture of purified BuMECs.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study [ 111 ] on BuMECs, it was revealed that the enzyme elongase (responsible for long-chain fatty acid synthesis) promotes lipid synthesis during lactation by synthesizing long-chain fatty acids and also regulating the expression levels of other related genes for milk fat synthesis during lactation. A comparative proteome study of exosome-derived proteins (exosomes isolated from cultured bovine mammary epithelial cells (BMECs) and milk) revealed the involvement of exosome proteins in signaling pathways regulating the lactation process [ 112 ].…”
Section: Structural and Functional Development Of The Bovine Mammary ...mentioning
confidence: 99%
“…Overexpression or interference ELOVL6 can promote the expression of FASN in BMECs and also has positive regulatory effects on insulin-induced genes (INSIG1 and INSIG2), SREBP1 and PPARG. So, we hypothesized that ELOVL6 could rely on transcription factors INSIG, SREBP1 and PPARG to regulate FASN ( 51 ). cAMP responsive element binding protein 1 (CREB1) is a member of the leucine zipper transcription factor family of DNA binding proteins, which is involved in the regulation of cellular lipid metabolism ( 52 ).…”
Section: Positive Regulation Of De Novo Synthesis Of Famentioning
confidence: 99%
“…In addition, ELOVL6, EGFR and THRSP also have positively regulated SCD1. The regulation of SCD1 by EGFR depends on the AKT- and PLC-γ-1 signaling pathways ( 38 , 51 , 56 ).…”
Section: Lcfa Transport and Desaturationmentioning
confidence: 99%
See 1 more Smart Citation